EFFECT OF PAPRIKA CRYSTALS ON AGE RELATEDMACULAR DEGENERATION- A CELL CULTURE STUDY - SREERAJ GOPI,; JOBY JACOB,; JITHIN RAJ KK,; SHINTU JUDE, (International Journal of Pharma and Bio Sciences, 2016)
Carotenoids are responsible for the color of chilly. In the present study, the carotenoids were separated from chilly as paprika crystals, and developed a formulation to enhance its bioavailability. A comparative cell culture study was conducted on the effect of paprika crystal carotenoids on age related macular degeneration. The current study proves efficacy of the new formulation.